Using ohmic heating to shorten the tempering time for frozen fish - Teerin Chysirichote; Nahathai Phumchom; Sappayakorn Chintapum; Worasuang Klinthong; Kazuhisa Ohtaguchi; Tipaporn Yoovidhya (International Journal of Food Science & Technology, 2023)
Summary Thawing is necessary to restore the freshness of fish before cooking because fish is often frozen to retain its freshness. Frequently, fish is partially thawed (or ‘tempered’) as it is easier to handle in this form than fully thawed fish. However, the conventional tempering techniques – immersion in water and still air tempering – take a long time and alter the fish's characteristics. Hence, the aim of this study was to use the heat generated inside the frozen fish, or ohmic heating, to alter the tempering process. Compared with conventional tempering operations, in this study, three voltage levels (20, 30 and 40 V/cm) were used for ohmic tempering. The fish quality and yield findings revealed that 30‐V/cm ohmic heating was more appropriate, even though ohmic heating at 40 V/cm provided the shortest tempering time. The main operating expense for ohmic tempering was the power cost of USD 58.5/100 kg, whereas the major operating expense for water immersion was the cost of water supply and wastewater treatment, which was around USD 108/100 kg. By using ohmic heating instead of still air and water immersion to temper the frozen fish, not only was less time required while retaining the freshness of the fish but the cost of tempering was also reduced.
Keywords: Aquaculture Nutrition and Growth; Meat and Animal Product Quality